Getting wise to the Web - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
advanced course on Web design and the use of databases organised by CTA in collaboration with the Tanzanian Commission on Science and Technology in September 2000 in Dar es Salaam